RIWAYAT INISIASI MENYUSUI DINI DENGAN KEJADIAN DIARE PADA BAYI USIA 0-12 BULAN - Veranita Nindi Probo Utami; Ida Erni Sipahutar (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
The aim of this study was to determine the relationship between the history of early breastfeeding initiation and the incidence of diarrhea in infants aged 0-12 months in Wangaya Hospital in 2019. The method was quantitative observational analytic and cross sectional approach using consecutive sampling. The number of samples is 48 people. The study was conducted in April-May 2019. Data collection used questionnaire of history early breastfeeding initiation and medical records. The results showed that the majority of infants aged 7-12 months were 54.2% and female were 52.1%. Most babies have a history of initiation of early breastfeeding which is quite 45.8%. Most babies experience severe dehydration diarrhea which is 37.5%. Hypothesis testing uses the spearman test with p-value = 0.001 (α = 0.05) and r = -0.729. Suggestion:Nurse to consider doing health promotion about diarrhea preventing and early initiation breasfeastfeeding benefits so could decrease incidents diarrhea prevalence in infants.